Structural synthesis of terminal control using acceleration energy - Andrey A. Kostoglotov (Advanced Engineering Research, 2015)
Considerations of the system physical features in the form of its invariants allow advancing in the solution of the problem of terminal control structural synthesis. It is achieved by using the acceleration energy when forming an extended objective functional that determines the difference of the obtained result from the known ones. The application of the device of asynchronous variation has led to the establishment of the necessary and sufficient conditions for a minimum target functional. On its basis, the boundary-value problem equations for Appell dynamic systems are obtained. Their final form is determined by the synthesis purpose. The development of these equations should be performed for specific cases. The validity of the results obtained is confirmed by the results of the terminal control problem solution. For linear systems, the offered method allows obtaining the exact analytical solution. The synthesized control provides the nonimpact change mode of the dynamic system condition.